Studi Perhitungan Laju Reaksi Neutron Dalam Reaktor SCWR (Supercritical Water Reactor) Model Perangkat (Assembly) Heksagonal Berbahan Bakar Thorium - Apriliana Apriliana; Yanti Yulianti; Pulung Karo Karo (Jurnal Teori dan Aplikasi Fisika, 2018)
The calculation of fission and capture reaction rate with and without filter has been done using REACT of SRAC. In material 1 fission reaction rate with and without filter were increased by increasing percent of U233. The highest fission reaction rate with filter was 5,7194x10-2reaction/cm3sand without filter was 6,1361x10-2 reaction/cm3s. Meanwhile capture reaction rate with and without filter were decreased by increasing percent of U233. The highest capture reaction rate with filter was 2,2156x10-2 reaction/cm3s and without filter was 2,4906x10-2 reaction/cm3s. In material 3, fission and capture reaction rate with and without filter were decreased by increasing percent of U233 in material 1. The highest fission reaction rate with filter was 1,5218x10-2 reaction/cm3s and without filter was 1,6293x10-2reaction/cm3s. The highest capture reaction rate with filter was 2,2156x10-2 reaction/cm3s and without filter was 2,3993x10-2reaction /cm3s. Neutron reaction rate with filter was smaller than neutron reaction rate without filter